Implementasi Pembiayaan Murabahah Berdasarkan PSAK No 102 Terhadap Produk Mitraguna di Bank Syariah Indonesia KCP Situbondo Basuki Rahmat - Achmad Achmad; Kiptiyah Kiptiyah; Ach. Zukin (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2024)
Sharia Bank is a financial institution whose main business is providing credit and other services in accordance with sharia principles. Financing based on sharia principles is the provision of money or equivalent bills based on an agreement between the bank and another party and returning the money or bills after a certain period of time with compensation or profit sharing. Sharia banks have provided various conveniences and benefits in offering their facilities to the public so they are interested. One of them is consumer financing. To meet consumer needs, Mitraguna products are financing products that help meet all customer needs for purchasing certain goods. The focus of this research is how to implement the murabahah contract on partner financing products and whether the implementation of the murabahah contract on partner financing products at Bank Syariah Indonesia KCP Situbondo Basuki Rahmat is in accordance with PSAK No. 102.The purpose of this research is to determine the application of the murabahah contract on partner products and to determine the suitability of implementing the murabahah contract on partners at Bank Syariah Indonesia KCP Situbondo Basuki Rahmat based on PSAK No. 102. This type of research is field research using qualitative methods with a descriptive approach. Data obtained through the process of observation, semi-structured interviews and documentation. Then the data obtained is processed through three stages, namely, data reduction, data presentation, and drawing conclusions. Data validity was carried out by testing data credibility and theory triangulation.The results of this research show that the implementation of the murabahah contract on partner products at Bank Syariah Indonesia KCP Situbondo Basuki Rahmat is implementing a sale and purchase contract or murabahah with the type of murabahah without orders. The bank does not have product inventory so it is necessary for the customer to carry out the Mitraguna financing proposal and then the bank will buy the goods or needs that the customer wants. And the implementation of murabahah contracts on partner products is in accordance with PSAK No. 102 at Bank Syariah Indonesia KCP Situbondo Basuki Rahmat, overall regarding the recognition and measurement, presentation and journal disclosure of murabahah transactions for counterparty products is in accordance with PSAK No. 102.